2021
DOI: 10.1038/s41598-021-01627-2
|View full text |Cite
|
Sign up to set email alerts
|

Immune classification and identification of prognostic genes for uveal melanoma based on six immune cell signatures

Abstract: Cutaneous melanoma could be treated by immunotherapy, which only has limited efficacy on uveal melanoma (UM). UM immunotyping for predicting immunotherapeutic responses and guiding immunotherapy should be better understood. This study identified molecular subtypes and key genetic markers associated with immunotherapy through immunosignature analysis. We screened a 6-immune cell signature simultaneously correlated with UM prognosis. Three immune subtypes (IS) were determined based on the 6-immune cell signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…CHL1 was found to be one of the most downregulated genes in UM that metastasized to the liver compared to non-metastatic tumors [22]. ROPN1 has previously been described as related to good prognosis when overexpressed in the UM TCGA dataset [23]; however, in the Piaggio et al dataset [17], several metastatic patients have high expression levels of this gene (Figures S2 and S3). Among the genes selected by CNAPE and DF, we can find several genes related to worse prognosis.…”
Section: Integration Of Resultsmentioning
confidence: 82%
“…CHL1 was found to be one of the most downregulated genes in UM that metastasized to the liver compared to non-metastatic tumors [22]. ROPN1 has previously been described as related to good prognosis when overexpressed in the UM TCGA dataset [23]; however, in the Piaggio et al dataset [17], several metastatic patients have high expression levels of this gene (Figures S2 and S3). Among the genes selected by CNAPE and DF, we can find several genes related to worse prognosis.…”
Section: Integration Of Resultsmentioning
confidence: 82%
“…The characteristics of immune infiltration have been explored in tumors stratified into different risk groups based on prognostic factors. For instance, three immune subtypes have been determined based on a signature comprising six immune types of cells associated with the prognosis of uveal melanoma ( 95 ). Immune subtype 3 had the highest LDA score that reflected a response to anti-PD1 immunotherapy, where immune subtype 1 had the lowest LDA score reflecting an immunosuppressive phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…BEX5 belongs to the human brain-expressed X-linked family, which played an essential role in the cell cycle and apoptosis. [21] Although the function of other members of the BEX family was confirmed as an oncogene or tumor suppressor, [22][23][24][25] and studies showed that BEX5 was lowly expressed and related to the poor prognosis in uveal melanoma and lung adenocarcinoma, [21,26] there were fewer studies about the effect of BEX5 on the progress of cancers. In this study, we found BEX5 was significantly downregulated in the THCA tissues compared with normal tissues because of the CNV to some extent.…”
Section: Discussionmentioning
confidence: 99%